OPTIMIZATION DATA ANALYSIS OF LAND FUEL TRANSPORTER VENDOR SELECTION USING THE SIMPLE ADDITIVE WEIGHTING METHOD AT PT.XYZ - Pradana, Muhammad Arya Rizky; Prastiwi, Karina Ramadani; Pratama, Rendy Bagus (Jurnal Disprotek, 2025)
This study aims to optimize the selection of land transportation vendors for fuel oil (BBM) at PT. XYZ using the Multi Criteria Decision Making (MCDM) method with the Simple Additive Weighting (SAW) technique. Land transportation of fuel oil (BBM) has a high complexity that involves aspects of safety, delivery reliability, and compliance with HSSE standards. PT. XYZ faces challenges such as delivery delays and safety risks that can disrupt distribution continuity. The SAW method was chosen to evaluate vendors objectively based on predetermined weighted main criteria, such as operational performance, fleet capacity, and service flexibility. The data used is existing vendor data, analyzed to produce systematic, transparent, and measurable vendor selection decisions. The results of the study are expected to provide strategic recommendations to improve the efficiency, safety, and reliability of fuel oil distribution at PT. XYZ, while supporting the principle of “Delivering Energy with Excellence” and strengthening national energy security in a sustainable manner. This approach places PT. XYZ in an adaptive position to future energy distribution challenges.ANALISIS DATA OPTIMASI PEMILIHAN VENDOR TRANSPORTIR BBM MODA DARAT DENGAN METODE SIMPLE ADDITIVE WEIGHTING DI PT.XYZ  Penelitian ini bertujuan mengoptimalkan pemilihan vendor transportir Bahan Bakar Minyak (BBM) moda darat di PT. XYZ menggunakan metode Multi Criteria Decision Making (MCDM) dengan teknik Simple Additive Weighting (SAW). Distribusi BBM melalui moda darat memiliki kompleksitas tinggi yang melibatkan aspek keselamatan, keandalan pengiriman, dan kepatuhan terhadap standar HSSE. PT. XYZ menghadapi tantangan seperti keterlambatan pengiriman dan risiko keselamatan yang dapat mengganggu kontinuitas distribusi. Metode SAW dipilih untuk mengevaluasi vendor secara objektif berdasarkan kriteria utama yang telah ditentukan bobotnya, seperti performa operasional, kapasitas armada, dan fleksibilitas pelayanan. Data yang digunakan merupakan data vendor yang sudah ada, dianalisis untuk menghasilkan keputusan pemilihan vendor yang sistematis, transparan, dan terukur. Hasil penelitian diharapkan dapat memberikan rekomendasi strategis untuk meningkatkan efisiensi, keselamatan, dan keandalan distribusi BBM di PT. XYZ, sekaligus mendukung prinsip “Delivering Energy with Excellence” dan memperkuat ketahanan energi nasional secara berkelanjutan. Pendekatan ini menempatkan PT. XYZ pada posisi yang adaptif terhadap tantangan distribusi energi masa depan.